2013
DOI: 10.1155/2013/281723
|View full text |Cite
|
Sign up to set email alerts
|

Vibration and Acoustic Response of Rectangular Sandwich Plate under Thermal Environment

Abstract: In this paper, we focus on the vibration and acoustic response of a rectangular sandwich plate which is subjected to a concentrated harmonic force under thermal environment. The critical buckling temperature is obtained to decide the thermal load. The natural frequencies and modes as well as dynamic responses are acquired by using the analytical formulations based on equivalent non-classical theory, in which the effects of shear deformation and rotational inertia are taken into account. The rise of thermal loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…During heating period, compressive forces generate in the constrained plate, and the values increase with the increment of temperature. As reported in the previous studies [9][10][11][12][13][14], compressive thermal forces will reduce the stiffness of the plate, natural frequencies decrease under thermal loads. In the meanwhile, the clamped plate deflects in the process of heating, and the central deflection of the equilibrium position of the test plate gets larger as the temperature rises.…”
Section: Natural Vibrationsupporting
confidence: 52%
See 1 more Smart Citation
“…During heating period, compressive forces generate in the constrained plate, and the values increase with the increment of temperature. As reported in the previous studies [9][10][11][12][13][14], compressive thermal forces will reduce the stiffness of the plate, natural frequencies decrease under thermal loads. In the meanwhile, the clamped plate deflects in the process of heating, and the central deflection of the equilibrium position of the test plate gets larger as the temperature rises.…”
Section: Natural Vibrationsupporting
confidence: 52%
“…Responses were obtained based on the governing equation of plates with thermally induced membrane forces. Liu and Li [13] studied the response characters of rectangular sandwich plates with temperature variations. Equivalent non-classical theory with the shear and rotational inertia was used in the work.…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Li [7,8] investigate the vibration and acoustic response of a rectangular isotropic sandwich plate which is subjected to a concentrated harmonic force or acoustic excitation under thermal environment. The equivalent non-classical theory [9] is employed to obtain the governing equation under thermal environment.…”
Section: Introductionmentioning
confidence: 99%
“…What is worth mentioning is to take thermal effect into account when PC structures serve in thermal environment, since the impact of thermal load on the dynamic characteristic and noise reduction properties of structure cannot be neglected. [10][11][12][13] Recently, it starts to receive increasing attention that temperature variation may lead to the shift in PC band structure. For beginning, a number of studies were focused on the material properties which are sensitive to temperature such as the longitudinal (transverse) sound velocity, the Young's modulus et al 18,19 Besides that, Yao et al 15 found that the effect of thermal load on band gap is related to lattice form and material components by computing two dimensional PC plate though supercell-plane-wave-expansion-method.…”
Section: Introductionmentioning
confidence: 99%